Analysis of the Application of Bruner's Theory in Improving Mathematics Learning Outcomes in Geometry Materials at SD Negeri 14 Sei Meranti - Grace Theo Fanny Lumbanbatu; Atikah Dapriani Lubis; Sontioka Iyolanda Margaretha Lumban Tobing; Putri Sadaria Simangunsong; Laurensia M. Perangin Angin (Journal of Educational Analytics, 2023)
Bruner's learning theory is a student-centered discovery learning model. This study aims to determine the application of Bruner's theory in improving student mathematics learning outcomes. This study used qualitative research methods. Students learn through active engagement with concepts and principles, and teachers encourage students to gain experience by engaging in activities that allow them to discover concepts and principles for themselves. In using Brunner's theory in geometric learning it can be said to be successful because it helps students to understand and recognize the parts of geometric shapes and geometric materials. Based on these results, it means that the application of Bruner's theory can improve student learning outcomes in elementary school geometric learning.